2018
DOI: 10.1002/fes3.126
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a network describing asparagine metabolism in plants and its application to the identification of genes affecting asparagine metabolism in wheat under drought and nutritional stress

Abstract: A detailed network describing asparagine metabolism in plants was constructed using published data from Arabidopsis (Arabidopsis thaliana) maize (Zea mays), wheat (Triticum aestivum), pea (Pisum sativum), soybean (Glycine max), lupin (Lupus albus), and other species, including animals. Asparagine synthesis and degradation is a major part of amino acid and nitrogen metabolism in plants. The complexity of its metabolism, including limiting and regulatory factors, was represented in a logical sequence in a pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 112 publications
(155 reference statements)
2
41
0
1
Order By: Relevance
“…6D), which was although controlled through chemical pesticide but still might impact concentration of both amino acid in these lines. These results are in accordance with the study by Curtin et al, (2018) 43 who determined that free amino acid accumulation in the seed does vary considerably owing to the plant's response to different stresses. The elevation in the ZmASN activity may not reduce the asparagine concentration (asparagine synthetase activity is not inhibited) while at the same time, glutamic acid and glutamine concentrations are directly affected by this ZmASN activity.…”
Section: Phenotypic Analysis Of Transgenic Cotton Lines Though the Esupporting
confidence: 93%
“…6D), which was although controlled through chemical pesticide but still might impact concentration of both amino acid in these lines. These results are in accordance with the study by Curtin et al, (2018) 43 who determined that free amino acid accumulation in the seed does vary considerably owing to the plant's response to different stresses. The elevation in the ZmASN activity may not reduce the asparagine concentration (asparagine synthetase activity is not inhibited) while at the same time, glutamic acid and glutamine concentrations are directly affected by this ZmASN activity.…”
Section: Phenotypic Analysis Of Transgenic Cotton Lines Though the Esupporting
confidence: 93%
“…Overexpression of ASN1 in Arabidopsis was shown to increase the N status of the plant and seed protein content (Law et al, 2003). TaASN1 in wheat is the most responsive gene to N availability compared to the alternative ASN genes; TaASN2, TaASN3, TaASN4 (Curtis et al, 2018). A marker that overlapped with HORVU1Hr1G092130, encoding a WRKY transcription factor, was identified from the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Candidate genes retrieved from the significant MTAs belong to key gene families such as the asparagine synthetase (ASN) gene family, bHLH, WRKY, MADS and NAC transcription factors (TFs), protein kinases, and nitrate transporters. They have been reported as genes associated with N metabolism in maize, soybean, wheat, and Arabidopsis (Law et al, 2003;Hao et al, 2011;Curtis et al, 2018;Jiang et al, 2018). In our study, a gene encoding asparagine synthetase 2 (HvASN2) was identified on chromosome 1H.…”
Section: Discussionmentioning
confidence: 76%
“…+ -induced stress [71,72]. Furthermore, asparagine has been suggested to play a role in the response to many abiotic stresses, for example sulphur-and phosphate-deficiency, together with drought and salt stress [73,74]. Moreover, N can be redirected from glutamine to asparagine as a temporary measure to control excessive ammonium provision [75].…”
Section: Discussionmentioning
confidence: 99%